Hubungan Pengetahuan Ibu Hamil Tentang Infeksi Hepatitis B Dengan Kunjungan Antenatal Care (ANC) - Ali Mahmud; Qory Aina (Puslitbang Sinergis Asa Professional, 2023)
One effort that can be done to reduce the Maternal Mortality Rate (MMR) in Indonesia is Antenatal Care (ANC). ANC is carried out to detect conditions that lead to maternal death, prevent and treat these conditions as early as possible. Therefore ANC has an important role to reduce MMR in Indonesia. Efforts that can be made to increase ANC visits for pregnant women are to intervene in factors that can encourage pregnant women to perform ANC. One of these factors is the knowledge factor regarding the importance of ANC, for example knowledge about the urgency of hepatitis B infection and its prevention that can be done during ANC. Knowing the relationship between knowledge of pregnant women about HB-infection to Antenatal Care (ANC). The method used is the method of literature review. The results of the analysis show that there is a relationship between the knowledge of pregnant women about hepatitis B and ANC visits. There are at least 3 journals which explain that insufficient or insufficient knowledge about hepatitis B will influence pregnant women to take efforts to prevent the transmission of this infection, for example the prevention efforts included in the ANC program. There are several other studies that show the opposite results, namely the high number of ANC visits is not accompanied by high knowledge of hepatitis B infection in pregnant women.